Forensic engineering 2018. proceedings of the Eighth Congress on Forensic Engineering, November 29-December 2, 2018, Austin, Texas - Liu, Rui (Structural engineer); Lester, Michael P.; Díaz de León, Alicia; Drerup, Michael J. (American Society of Civil Engineers, 2018)
Contains 111 peer-reviewed papers on a wide array of forensic topics in the built environment, with some taking new approaches to historic failure events and others exploring new frontiers in forensic evaluation and analysis methods. Topics include: building envelopes; investigation methodologies; structural repair and remediation; vibration; performance of concrete and other materials; blast and extreme loading; hurricanes and earthquakes; failures during construction; and forensic engineering education and professional practice.